Aldehyde cellulose / keratin composite fiber as well as preparation method and application thereof
Through the composite technology of aldehyde-based cellulose and keratin, the problem of using biological resources such as wool waste and waste cotton to convert them into high-value-added composite fibers is solved, and the recyclability of resources is achieved, and the composite fibers are given excellent mechanical properties and ultraviolet resistance.
Patent Information
- Application Number
- CN202411754167.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-02-28
AI Technical Summary
The prior art is difficult to effectively utilize biological resources such as wool waste and waste cotton, and convert them into high value-added composite fibers, resulting in waste of resources and environmental pollution.
Aldehyde-based cellulose/keratin composite fibers are prepared by the composite technology of aldehyde-based cellulose and keratin. The method includes aldehyde-aggranulation of cellulose fibers and introducing aldehyde groups into the cellulose through sodium periodate oxidation reaction, and then modifying the keratin layer on the surface of the aldehyde-based cellulose fibers to achieve the complexation of the fibers and keratin.
The prepared aldehyde-based cellulose/keratin composite fiber has excellent mechanical properties, UV resistance and UV aging resistance, and can effectively utilize resources such as wool and cotton pulp to reduce environmental pollution.
Smart Images

Figure CN119531132A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite fiber preparation, and in particular to an aldehyde cellulose / keratin composite fiber, a preparation method and application thereof. Background Art
[0002] According to statistics, tens of millions of tons of wool waste and waste cotton are generated every year in the world. More than 80% of the substances in these waste wool are keratin, which is a resource with very high practical value and has good biocompatibility and biodegradability. Cellulose in waste cotton is the most abundant natural polymer in nature. It is commonly found in wood and plants and is commonly known as plant cellulose. Cellulose can also be synthesized by microbial methods, such as fungi and bacteria, and the synthesized cellulose is called bacterial cellulose. In addition, cellulose can be obtained from animals; for example, tunicates are the most well-known cellulose-containing animals. Regardless of the species or source, cellulose is composed of repeating glucose units (C6H 10 O5), and the hydroxyl groups can be modified with specific organic or inorganic chemicals to impart desired properties. In addition, cellulose is environmentally friendly, highly biocompatible and biodegradable.
[0003] Usually, a large amount of wool waste and waste quilts are converted into low-value products, such as feed additives or sewage treatment agents. If green processing technology is used to convert waste biological resources or textiles into high-value-added composite fibers, it can not only significantly reduce environmental pollution, but also alleviate resource waste, and the obtained fibers have certain application prospects in the textile industry.
[0004] In view of this, it is necessary to design an improved aldehyde cellulose / keratin composite fiber, a preparation method and application thereof to solve the above problems. Summary of the invention
[0005] The purpose of the present invention is to provide an aldehyde cellulose / keratin composite fiber, a preparation method and application thereof.
[0006] To achieve the above-mentioned object of the invention, on the one hand, the present invention provides an aldehyde cellulose / keratin composite fiber, comprising:
[0007] Aldehyde cellulose fibers;
[0008] The keratin layer covers the outside of the aldehyde-based cellulose fiber.
[0009] On the other hand, the present invention also provides a method for preparing the above-mentioned aldehyde cellulose / keratin composite fiber, comprising the following steps:
[0010] The raw wool is soaked in a sodium bicarbonate aqueous solution to obtain pretreated wool; the pretreated wool is cut and placed in the treatment solution, and after stirring for a certain period of time, the upper layer solution is collected by centrifugation, and after dialyzing, a wool keratin solution is obtained;
[0011] Dissolving cotton pulp in an ion solution, heating for a predetermined time under stirring conditions, adding sodium periodate to the mixed solution, introducing aldehyde groups onto cotton pulp fibers using sodium periodate, and centrifuging after the reaction to obtain an aldehyde cellulose solution; adopting a wet spinning method, using the aldehyde cellulose solution as a spinning stock solution to obtain aldehyde cellulose fibers;
[0012] The aldehyde-based cellulose fiber is immersed in the wool keratin solution and dried to obtain the composite fiber.
[0013] Preferably, the reaction time after adding sodium periodate is 0.5-3h; and the mass percentage of sodium periodate in the mixed solution is 2-3.5%.
[0014] Preferably, the aldehyde-based cellulose fibers are immersed in the wool keratin solution for 30-60 seconds.
[0015] Preferably, the concentration of the sodium bicarbonate aqueous solution is 0.6-1 mol / L, and the weight ratio of the wool to the sodium bicarbonate aqueous solution is 1:20.
[0016] Preferably, the treatment liquid is prepared from urea, sodium dodecyl sulfate, L-cysteine and water, the molar concentration of urea in the treatment liquid is 6-8 mol / L, the molar concentration of sodium dodecyl sulfate is 0.01-0.02 mol / L, and the amount of L-cysteine added is 10% of the mass of the wool.
[0017] Preferably, the ionic solution is 1-allyl-3-methylimidazolium chloride, and the mass percentage of the cotton pulp in the ionic solution is 2-3.5%.
[0018] Preferably, the stirring time after adding the wool into the treatment liquid is 4-6 hours, the stirring speed is 800-1500 rpm, the centrifugal time is 10-15 minutes, and the centrifugal speed is 7000-8000 rpm.
[0019] Preferably, the centrifugation time after the addition of sodium periodate is 3-5 min and the rotation speed is 7000-8000 rpm.
[0020] In particular, the aldehyde cellulose / keratin composite fiber prepared by the preparation method proposed in the present invention can be used to prepare anti-ultraviolet products.
[0021] The beneficial effects of the present invention are:
[0022] 1. The preparation method of aldehyde cellulose / keratin composite fiber provided by the present invention introduces aldehyde groups into cellulose by oxidizing cellulose with sodium periodate, so as to realize the composite of aldehyde cellulose and keratin by chemical bonding between aldehyde groups of cotton pulp fiber and amino groups of keratin. The composite fiber prepared by the above method has excellent mechanical properties, UV resistance and UV aging resistance.
[0023] 2. The preparation method of the aldehyde cellulose / keratin composite fiber provided by the present invention can accurately control the number of aldehyde groups introduced by adjusting the amount of sodium periodate added and the oxidation reaction time, thereby avoiding the introduction of too many aldehyde groups which may affect the mechanical properties of the cellulose fiber, thereby ensuring that the final composite fiber has excellent mechanical properties; by introducing the keratin layer, its excellent mechanical strength, UV resistance and other properties can be fully utilized, giving the composite fiber excellent UV resistance and UV aging resistance.
[0024] 3. The preparation method of the aldehyde cellulose / keratin composite fiber provided by the present invention uses low-cost wool and cotton pulp as raw materials, thus realizing the recycling of resources. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a production process flow chart of the preparation method of the aldehyde cellulose / keratin composite fiber proposed by the present invention;
[0026] Figure 2 This is a SEM image of the composite fiber prepared in Example 1 of the present invention;
[0027] Figure 3 This is an optical photograph of the composite fiber prepared in Example 1 of the present invention;
[0028] Figure 4 This is an optical photograph of a fabric woven with the composite fibers prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0030] It should also be noted that, in order to avoid obscuring the present invention due to unnecessary details, only structures and / or processing steps closely related to the scheme of the present invention are shown in the drawings, while other details that are not closely related to the present invention are omitted.
[0031] In addition, it should be noted that the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0032] The aldehyde cellulose / keratin composite fiber provided by the present invention comprises:
[0033] Aldehyde cellulose fibers;
[0034] A keratin layer of moderate thickness that covers the outside of the aldehyde-based cellulose fibers.
[0035] For further information, see Figure 1 As shown, the present invention also provides a method for preparing the above-mentioned aldehyde cellulose / keratin composite fiber, comprising the following steps:
[0036] Preparation of keratin solution: soaking raw wool in a sodium bicarbonate aqueous solution for degreasing, washing with deionized water, and drying to obtain pretreated wool; cutting the pretreated wool, putting it into the treatment solution, stirring it at 80-100° C. for a certain period of time, centrifuging and collecting the upper layer solution, and dialysis treatment to obtain the wool keratin solution;
[0037] Preparation of aldehyde cellulose fiber: dissolve cotton pulp in an ionic solution, heat under stirring conditions for 8-10 hours, add sodium periodate to the mixture, continue heating and stirring for 0.5-3 hours, and centrifuge to obtain an aldehyde cellulose solution; adopt a wet spinning method, use the aldehyde cellulose solution as the spinning solution, and ethanol as the coagulation bath to obtain aldehyde cellulose fiber;
[0038] Preparation of composite fiber: The aldehyde cellulose fiber is immersed in a wool keratin solution and then dried to obtain the composite fiber.
[0039] In the above technical scheme, a layer of keratin is modified on the surface of cellulose fiber after aldehyde modification, and the reaction between the aldehyde group on the fiber surface and the amino group in the keratin can be used to make the keratin molecules adsorbed on the fiber surface in an orderly manner, thereby realizing the combination of fiber and keratin. In this process, the reaction between the aldehyde group and the amino group can be used to form a cross-linked structure, and a keratin layer is evenly formed on the fiber surface. The formation of the keratin layer can serve as a physical barrier for ultraviolet light, effectively reflecting, scattering and absorbing ultraviolet radiation, and giving the composite fiber excellent anti-ultraviolet properties; at the same time, keratin itself has a certain mechanical strength, so the formation of the keratin layer can enhance the mechanical properties of cellulose fiber, and give the composite fiber excellent mechanical properties.
[0040] As an embodiment of the present invention, the weight ratio of wool to sodium bicarbonate aqueous solution is 1:20, the concentration of sodium bicarbonate aqueous solution is 0.6-1 mol / L, the degreasing time is 2-5 hours, and the drying temperature after washing with deionized water is 25-40°C.
[0041] As an embodiment of the present invention, the pH of the treatment liquid is 10-11, and it is prepared by urea, sodium dodecyl sulfate, L-cysteine and water, wherein the molar concentration of urea is 6-8 mol / L, the molar concentration of sodium dodecyl sulfate is 0.01-0.02 mol / L, and the amount of L-cysteine added is 10% of the mass of the wool. The mass of the wool in this step is 3-5g.
[0042] As an embodiment of the present invention, after adding the wool into the treatment liquid, the stirring time is 4-6 hours, the stirring speed is 800-1500 rpm, the centrifugal time is 10-15 minutes, and the centrifugal speed is 7000-8000 rpm.
[0043] As an embodiment of the present invention, the dialysis treatment conditions are: the time is 0-3 days, and the molecular weight cut-off of the dialysis bag is 3000-3500. To prevent the wool keratin solution from deteriorating, it can be stored in an environment of 0-5°C when not in use.
[0044] As an embodiment of the present invention, the ionic solution is 1-allyl-3-methylimidazolium chloride (AMIM-Cl ionic liquid), and the mass percentage of cotton pulp in the ionic solution is 2-3.5%. By using the above solution to treat the cotton pulp, damage to cellulose during the dissolution process can be avoided. At the same time, the AMIM-Cl ionic liquid is non-toxic and avoids damage to the environment.
[0045] As an embodiment of the present invention, during the dissolution of the cotton pulp, the heating temperature is 80-100° C. and the stirring speed is 800-1500 rpm.
[0046] As an embodiment of the present invention, the mass percentage of sodium periodate in the mixed solution is 2-3.5%; the centrifugation time after the sodium periodate is added is 3-5 minutes, and the rotation speed is 7000-8000rpm. It should be noted that after adding sodium periodate, in order to avoid its decomposition and affect the oxidation process of the fiber, the system can be placed in a light-shielding environment; in addition, in other embodiments, sodium periodate can also be replaced by other oxidizing substances, as long as the purpose of oxidizing cotton pulp fibers can be achieved.
[0047] In the above technical scheme, by adding sodium periodate, the secondary hydroxyl groups at the C2 and C3 positions in the cellulose molecules can be selectively oxidized to aldehyde groups, so that while maintaining the good properties of the cellulose itself, a new functional group - aldehyde group is introduced, which provides an active site for the functional modification of cellulose and effectively broadens the application range of cellulose; at the same time, by regulating the amount of sodium periodate added and the stirring time after the addition of sodium periodate, the degree of hydroxyl oxidation reaction in the above cellulose molecules can be regulated to avoid destroying the molecular structure of cellulose in the process of introducing aldehyde groups to cellulose, thereby affecting the strength / rigidity of the composite fiber. This is because when too many aldehyde groups are introduced to cellulose, the molecular structure of the original cellulose may be destroyed and the crystallinity of cellulose may be reduced, thereby affecting the mechanical properties of cellulose.
[0048] As an embodiment of the present invention, the temperature of the spinning process is 25-40° C., and the injection flow rate of the syringe is 0.1-0.2 mL / m.
[0049] As an embodiment of the present invention, the immersion time of the aldehyde cellulose fiber in the wool keratin solution is 30-60s. By controlling the immersion time within the above range, the loading amount of the wool keratin can be adjusted. In the actual operation process, multiple immersions can be performed as needed, and each immersion is completed and dried before the next immersion. If the immersion time is too long, on the one hand, it will affect the air permeability of the inner layer of cellulose fibers. Secondly, with long immersion, the loading amount of the wool keratin increases, and uneven loading is prone to occur, affecting the stability and uniformity of the composite fiber.
[0050] In particular, the aldehyde cellulose / keratin composite fiber prepared by the preparation method proposed in the present invention has excellent UV resistance and UV aging resistance, and can therefore be used in sunscreen products, sunscreen clothing, indoor and outdoor decoration materials and other fields that require sunscreen performance.
[0051] The following is a further description of the aldehyde cellulose / keratin composite fiber, its preparation method and application proposed by the present invention in conjunction with specific embodiments:
[0052] Example 1
[0053] This embodiment prepares an aldehyde cellulose / keratin composite fiber, comprising the following steps:
[0054] Preparation of keratin solution: The raw wool was immersed in a 0.2 mol / L sodium bicarbonate aqueous solution for 2 h to degrease the wool, with a weight ratio of wool to solution of 1:20. The wool was taken out and washed with deionized water, and then dried at 35°C for 12 h. Then, 5 g of the degreased wool was cut and immersed in a 100 mL aqueous solution containing 8 mol / L urea, 0.02 mol / L SDS and L-cysteine (10%, based on the weight of the wool), and a 5 mol / L NaOH solution was added dropwise to adjust the pH to 10.6-11. Then, the mixed solution was magnetically stirred at 90°C for 4 h to completely dissolve the wool, and then the mixed solution containing the dissolved wool was centrifuged at a speed of 8000 rpm for 15 min, and the upper clear green solution was collected. Finally, the wool was dialyzed with deionized water (3500 Da cellulose dialysis bag) at 25°C for 3 days to remove urea and small molecule peptides to obtain a wool keratin solution, and the wool keratin solution was placed in a 5°C refrigerator for further use.
[0055] Preparation of aldehyde cellulose fiber: 0.5g cotton pulp is added to 24.5g AMIM-Cl ionic liquid, and stirred at 1000rpm for 8h at 80℃; then, a certain amount of sodium periodate is added to the mixed solution under shading conditions, and the mixture is stirred at 80℃ for 0.5h, and aldehyde groups are introduced into the cotton pulp fiber by the reaction between sodium periodate and cotton pulp fiber. After the reaction is completed, the mixture is centrifuged at 25℃ for 5min to obtain transparent and viscous aldehyde cellulose; the spinning stock solution is loaded into a syringe, and extruded into a coagulation bath (anhydrous ethanol) at a rate of 0.1mL / h through a 21G needle at 25℃, and dried in the sun to obtain aldehyde cellulose fiber; wherein the mass percentage of cotton pulp in the ionic solution is 3.5%, the mass percentage of sodium periodate in the mixed solution is 3.5%, and the centrifugal speed is 8000rpm;
[0056] Preparation of composite fiber: The aldehyde cellulose fiber is immersed in the wool keratin solution for 60 seconds, taken out and dried in the sun, and the aldehyde / wool keratin composite fiber is obtained after repeated immersion and drying in the sun for 5 times. It should be noted that the reagents used in this scheme can be obtained by commercial purchase unless otherwise specified.
[0057] The SEM image of the composite fiber prepared in this embodiment is as follows: Figure 2 As shown in the figure, it can be seen that keratin is successfully coated on the fiber surface. The optical photo of the composite fiber is shown in Figure 3 shown.
[0058] Examples 2 to 6
[0059] The difference between Examples 2 to 6 and Example 1 is only that: in the preparation process of aldehyde-based cellulose fiber, the stirring time after adding sodium periodate is different from that in Example 1, and the other experimental parameters are the same as those in Example 1, which will not be repeated here. The stirring time of Examples 1 to 6 and the performance comparison of the composite fibers prepared under the corresponding conditions are shown in Table 1. From the data in the table, it can be seen that with the increase of stirring time, the fracture strain and stress of the composite material are reduced. This is because: with the extension of stirring time (reaction time), the introduction of too many aldehyde groups on cellulose may destroy the molecular structure of the original cellulose, especially the hydrogen bonds between cellulose molecules or the long-range ordered structure of the molecular chain. Excessive reaction may even cause the cellulose molecular chain to break or shorten, which will directly affect the fracture strain and stress of the fiber; secondly, the introduction of aldehyde groups may break the crystalline region of cellulose and reduce its crystallinity. The reduction in crystallinity leads to a decrease in the rigidity of cellulose, which is manifested as a decrease in the fracture strain and stress of the fiber.
[0060] It should be noted that the mechanical property test of the present invention is obtained using a 5943 universal material testing machine from INSTRON Corporation of the United States. Before the test, the composite fiber is balanced for 12 hours under an environment of 23°C and 65% humidity. During the test, the sample stretching speed is 20 mm / min and the test length is 20 mm, that is, under pre-tension, the length of the fiber sample is 20 mm.
[0061] Table 1 Stirring time of Examples 1 to 6 and properties of composite fibers obtained under corresponding conditions
[0062] project Stirring time (h) Fracture stress (MPa) Fracture strain (%) Example 1 0.5 135.43 44.34 Example 2 1 120.43 40.74 Example 3 1.5 102.56 36.67 Example 4 2 86.86 32.95 Example 5 2.5 69.65 27.78 Example 6 3 59.78 20.73
[0063] Comparative Example 1
[0064] This comparative example prepares a pure cellulose fiber, comprising the following steps:
[0065] 0.5 g of cotton pulp was added to 24.5 g of AMIM-Cl ionic liquid, stirred at 80 ° C for 8 h, and then centrifuged at 25 ° C for 5 min with a centrifugal speed of 8000 rpm to obtain a transparent and viscous pure cellulose fiber spinning solution; then, the spinning solution was loaded into a syringe, the syringe was heated to 80 ° C and extruded into a coagulation bath (anhydrous ethanol) through a 21G needle at an extrusion rate of 0.1 mL / h, and dried in the sun to obtain pure cellulose fibers.
[0066] Comparative Example 2
[0067] This comparative example prepares an aldehyde-based cellulose fiber, comprising the following steps:
[0068] 0.5 g of cotton pulp was added to 24.5 g of AMIM-Cl ionic liquid, and stirred at 1000 rpm for 8 h at 80 ° C. Then, a certain amount of sodium periodate was added to the mixed solution under shading conditions, and stirred at 80 ° C for 1 h. Aldehyde groups were introduced into the cotton pulp fibers by the reaction between sodium periodate and cotton pulp fibers. After the reaction was completed, centrifugation was performed at 25 ° C for 5 min to obtain transparent and viscous aldehyde cellulose; the spinning stock solution was loaded into a syringe, and extruded into a coagulation bath (anhydrous ethanol) at an extrusion rate of 0.1 mL / h through a 21G needle at 25 ° C., and dried in the sun to obtain aldehyde cellulose fibers; wherein the mass percentage of cotton pulp in the ionic solution was 3.5%, the mass percentage of sodium periodate in the mixed solution was 3.5%, and the centrifugal speed was 8000 rpm.
[0069] Comparative Example 3
[0070] This comparative example prepares a pure cellulose / keratin composite fiber. The only difference between comparative example 3 and example 2 is that no aldehyde group is introduced into the cellulose, that is, no sodium periodate is added during the preparation of the cellulose fiber. The specific preparation steps are as follows:
[0071] The raw wool was immersed in 500 mL of 0.2 mol / L sodium bicarbonate aqueous solution for 2 h to degrease the wool, with a weight ratio of wool to solution of 1:20. The wool was taken out and washed with deionized water, and then dried at 35°C for 12 h. Then, 5 g of the degreased wool was cut and immersed in 100 mL of an aqueous solution containing 8 mol / L urea, 0.02 mol / L SDS and L-cysteine (10%, based on the weight of the wool), and 5 mol / L NaOH solution was added dropwise to adjust the pH to 10.6-11. Then, the mixed solution was magnetically stirred at 90°C for 4 h to completely dissolve the wool, and then the mixed solution containing the dissolved wool was centrifuged at 8000 rpm for 15 min to collect the clear green solution on the upper layer. Finally, the keratin solution was obtained by dialyzing with deionized water (3500 Da cellulose dialysis bag) at 25°C for 3 days to remove urea and small molecule peptides, and the keratin solution was placed in a 5°C refrigerator for further use.
[0072] 0.5 g of cotton pulp was added to 24.5 g of AMIM-Cl ionic liquid, stirred at 80 ° C for 8 h, and then centrifuged at 25 ° C for 5 min with a centrifugal speed of 8000 rpm to obtain a transparent and viscous pure cellulose fiber spinning solution; then, the spinning solution was loaded into a syringe, the syringe was heated to 80 ° C and extruded into a coagulation bath (anhydrous ethanol) through a 21G needle at an extrusion rate of 0.1 mL / h, and dried in the sun to obtain pure cellulose fibers.
[0073] The cellulose fibers were immersed in the keratin solution for 60 seconds, taken out and air-dried, and the immersion and air-drying were repeated 5 times to obtain pure cellulose / keratin composite fibers.
[0074] The performance comparison of the composite fibers prepared under the corresponding conditions in Comparative Examples 1 to 3 is shown in Table 2. From the data in the table, it can be seen that the mechanical properties of the pure cellulose fiber of Comparative Example 1 and the pure cellulose / keratin composite fiber of Comparative Example 3 are basically unchanged after being soaked in keratin, which indirectly indicates that keratin is basically not coated on the fiber surface. Compared with the aldehyde cellulose fiber of Comparative Example 2 and the aldehyde cellulose / keratin composite fiber of Example 2, the surface-coated keratin layer can effectively improve the surface toughness of the composite fiber and enhance its mechanical properties.
[0075] Table 2 Properties of composite fibers prepared under corresponding conditions in Comparative Examples 1 to 3
[0076]
[0077]
[0078] The anti-ultraviolet properties of the composite fibers prepared in Example 2 and Comparative Examples 1-3 are shown in Table 3. The results show that the T UVA , T UVB and T UVC It is lower than that of comparative examples 1-3, indicating that the composite fiber prepared by the preparation method proposed in the present invention has excellent anti-ultraviolet performance; the experimental results of anti-ultraviolet aging performance are shown in Table 4, the aging time is 72h, and it can be seen from the data in the table that the breaking stress and breaking stress of the composite fiber prepared in Example 2 are slightly reduced after aging for 72h, indicating that the chemical structure of the composite fiber has not changed, while the breaking stress and breaking stress of the fabric woven from pure cellulose fiber and aldehyde cellulose fiber are significantly reduced after aging for 72h. The results show that the aldehyde / wool keratin composite fiber fabric prepared by the present invention has excellent anti-ultraviolet aging performance.
[0079] Furthermore, the absorbance and transmittance of DACK were measured by the above-mentioned UV-visible near-infrared spectrophotometer (UV-3600Plus, Shimadzu, Japan) to analyze the UV resistance of DACK. The scanning wavelength range was 200-400nm, and the slit width was 20nm; the UV1000F (ultraviolet transmittance fabric analyzer) of Labsphere Company of the United States was used to measure the T of the fabric according to the Chinese standard GB / T 18830-2009. UVA , T UVB The sample is placed in front of the entrance of the integrating sphere. The transmittance is recorded every 5 nm, and then T is calculated according to formulas (1)-(3) UVA, T UVB and UPF value,
[0080] Where E(γ) represents the irradiance of light, in W / m 2 ; ε(γ) represents the relative erythema effect; T i (γ) represents the transmittance of the sample when the wavelength is γ; Δ(γ) is the wavelength interval, the unit is nm.
[0081] The anti-ultraviolet stability test was measured by a QUV / spray UV aging tester (Q-LAB, USA) with an irradiance of 500W. During the test, the sample was spread out at a distance of 20cm from the light source and tested at a wavelength of 302nm for 72h.
[0082] Table 3 Anti-ultraviolet properties of composite fibers obtained in Example 2 and Comparative Examples 1-3
[0083]
[0084]
[0085] Table 4 Anti-ultraviolet aging performance of composite fibers obtained in Example 2 and Comparative Examples 1-3
[0086] project Example 2 Comparative Example 1 Comparative Example 2 Comparative Example 3 Aging time (h) 72 72 72 72 Fracture stress before aging (MPa) 121.6±1.1 151.7±1.4 107.4±1.5 152.6±1.4 Fracture stress after aging (MPa) 117.8±1.2 128.2±1.2 83.5±1.3 125.6±1.2 Fracture strain before aging (%) 40.7±0.5 45.3±1.1 37.5±1.2 45.5±1.1 Fracture strain after aging (%) 39.1±0.4 40.4±1.1 29.5±0.9 39.8±1.1 Reduction of fracture stress (%) 3.1±0.1 15.5±1 22.3±1.4 17.7±1 Reduction of fracture strain (%) 3.9±0.2 10.9±0.8 21.4±1.2 12.4±0.8
[0087] In order to further explore the performance of the composite fibers obtained in Example 2 and Comparative Examples 1-3 during use, they were woven into fabrics. The optical photograph of the fabric obtained in Example 2 is as follows: Figure 4 As shown in Table 5, the experimental results of the ultraviolet protection factor (UPF) of the fabrics prepared under different conditions are shown in Table 5. It can be seen from the data in the table that the composite fiber prepared in Example 2 has a higher UPF value. UPF is the anti-ultraviolet index of textiles. According to a report from the School of Textile Science and Technology of the University of South Wales, Australia, when humans are exposed to the sun, the maximum time for skin erythema to occur is about ten minutes; if you wear clothes with UPF20, the time for erythema to occur can be extended by twenty times to two hundred minutes (more than three hours); similarly, if you bring an umbrella with UPF30, the time for skin erythema to occur can be extended by 30 times to three hundred minutes (five hours). The results show that the aldehyde / wool keratin composite fiber fabric prepared in the present invention has excellent anti-ultraviolet performance.
[0088] In the anti-ultraviolet aging performance experiment, the aging time was 72 hours, and the UPF values of the fabrics before and after aging were compared. The experimental results are shown in Table 5. The results show that the UPF value of the fabric obtained by the composite fiber prepared in Example 2 did not change substantially after aging for 72 hours, while the UPF value of the fabrics made of pure cellulose fibers and pure aldehyde cellulose fibers decreased significantly after aging for 72 hours.
[0089] Table 5 Experimental results of fabric UV protection factor
[0090]
[0091]
[0092] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.
Claims
1. An aldehyde cellulose / keratin composite fiber, characterized in that: include: Aldehyde cellulose fibers; The keratin layer covers the outside of the aldehyde-based cellulose fiber.
2. A method for preparing aldehyde cellulose / keratin composite fibers, characterized in that: The steps include: The raw wool is soaked in a sodium bicarbonate aqueous solution to obtain pretreated wool; the pretreated wool is cut and placed in the treatment solution, and after stirring for a certain period of time, the upper layer solution is collected by centrifugation, and after dialyzing, a wool keratin solution is obtained; Dissolving cotton pulp in an ion solution, heating for a predetermined time under stirring conditions, adding sodium periodate to the mixed solution, introducing aldehyde groups onto cotton pulp fibers using sodium periodate, and centrifuging after the reaction to obtain an aldehyde cellulose solution; adopting a wet spinning method, using the aldehyde cellulose solution as a spinning stock solution to obtain aldehyde cellulose fibers; The aldehyde-based cellulose fiber is immersed in the wool keratin solution and dried to obtain the composite fiber.
3. The preparation method according to claim 1, characterized in that: The reaction time after adding sodium periodate is 0.5-3h; the mass percentage of sodium periodate in the mixed solution is 2-3.5%.
4. The preparation method according to claim 1, characterized in that: The aldehyde-based cellulose fibers are immersed in the wool keratin solution for 30-60 seconds.
5. The preparation method according to claim 1, characterized in that: The concentration of the sodium bicarbonate aqueous solution is 0.6-1 mol / L, and the weight ratio of the wool to the sodium bicarbonate aqueous solution is 1:
20.
6. The preparation method according to claim 1, characterized in that: The treatment liquid is prepared from urea, sodium dodecyl sulfate, L-cysteine and water. The molar concentration of urea in the treatment liquid is 6-8 mol / L, the molar concentration of sodium dodecyl sulfate is 0.01-0.02 mol / L, and the amount of L-cysteine added is 10% of the mass of the wool.
7. The preparation method according to claim 1, characterized in that: The ion solution is 1-allyl-3-methylimidazolium chloride, and the mass percentage of the cotton pulp in the ion solution is 2-3.5%.
8. The preparation method according to claim 1, characterized in that: After the wool is added to the treatment liquid, the stirring time is 4-6 hours, the stirring speed is 800-1500 rpm, the centrifugal time is 10-15 minutes, and the centrifugal speed is 7000-8000 rpm.
9. The preparation method according to claim 1, characterized in that: The centrifugation time after the addition of sodium periodate is 3-5 minutes and the rotation speed is 7000-8000 rpm.
10. Use of the aldehyde cellulose / keratin composite fiber according to claim 1 or the aldehyde cellulose / keratin composite fiber prepared by the preparation method according to any one of claims 2 to 9 in the preparation of anti-ultraviolet products.